Analisis Pengaruh Gaya Kepemimpinan Dan Mutasi Terhadap Kinerja Pegawai Kantor Ksop Kelas I Panjang Yang Dimediasi Oleh Motivasi Kerja - Ratu Afaf; Faurani I Santi Singagerda (Hikamatzu | Journal of Multidisciplinary, 2026)
This study aims to analyze the influence of leadership style and transfer on employee performance with work motivation as a mediating variable at the KSOP Kelas I Panjang Office in Bandar Lampung. This research is motivated by the phenomenon of inconsistencies in previous research results as well as the problems of employee performance influenced by leadership, transfer, and work motivation factors. The research method used is a quantitative approach with data collection techniques through questionnaires distributed to 101 employees. Data analysis was conducted using multiple linear regression and the Sobel test to examine the mediating role. The research results show that leadership style does not have a significant effect on work motivation, but it has a positive and significant effect on employee performance. Meanwhile, transfers have a positive and significant effect on both work motivation and employee performance. Work motivation is also proven to have a positive and significant effect on employee performance. In mediation testing, motivation is unable to mediate the effect of leadership style on employee performance, but it is able to mediate the effect of transfers on employee performance